Migrationsgesellschaftliche Erinnerungsorte auf heimatkritischer Grundlage : Konturen eines Didaktisierungskonzeptes für die Erwachsenenbildung DaF/DaZ - Johannes Köck (Brünner Beiträge zur Germanistik und Nordistik, 2022)
This paper aims to outline a dissertation project, which was presented at the conference Aktuelle landeskundliche Ansätze in DaF/DaZ (Actual cultural studies on didactic in German as a foreign language and second language). Furthermore, I want to conceptualize two terms, that focus to this perspective – migrationssensibel (migrational sensitive) and heimatkritisch (home critic). The paper starts with a short historical overview and a debate on the role of the concepts of Landeskunde and Erinnerungsorte (Spaces of memory). It also presents the methodological design that will be used for this dissertation project (Grounded Theory, and City Walks). Finally, I will describe the expected outcome of this dissertation project.